2021
DOI: 10.3390/jpm11050421
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Medicine Based on Nasal Epithelial Cells: Comparative Studies with Rectal Biopsies and Intestinal Organoids

Abstract: As highly effective CFTR modulator therapies (HEMT) emerge, there is an unmet need to find effective drugs for people with CF (PwCF) with ultra-rare mutations who are too few for classical clinical trials and for whom there are no drug discovery programs. Therefore, biomarkers reliably predicting the benefit from CFTR modulator therapies are essential to find effective drugs for PwCF through personalized approaches termed theranostics. Here, we assess CFTR basal function and the individual responses to CFTR mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
(81 reference statements)
2
11
0
Order By: Relevance
“…Influential papers by Dekkers et al. ( Berkers et al., 2019 ; Fawcett et al., 2021 ; Ramalho et al., 2021 ; Silva et al., 2020 , 2021 ) highlighted the potential for the rectal organoid model to facilitate drug development and precision medicine for CF. Stem cells in the rectal mucosa provide a renewable source of this tissue, and biobanks of intestinal organoids from CF populations have been created around the world to enhance CF therapy development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influential papers by Dekkers et al. ( Berkers et al., 2019 ; Fawcett et al., 2021 ; Ramalho et al., 2021 ; Silva et al., 2020 , 2021 ) highlighted the potential for the rectal organoid model to facilitate drug development and precision medicine for CF. Stem cells in the rectal mucosa provide a renewable source of this tissue, and biobanks of intestinal organoids from CF populations have been created around the world to enhance CF therapy development.…”
Section: Introductionmentioning
confidence: 99%
“…The use of primary, patient-derived nasal cultures in preclinical studies of CFTR modulators has been highly informative ( Keegan and Brewington, 2021 ; Laselva et al., 2021a , 2021b ; Oren et al., 2021 ; Park et al., 2020 ; Phuan et al., 2021 ; Veit et al., 2020 ). Interestingly, Amaral's group demonstrated a correlation between CFTR rescue by CFTR modulators in primary nasal epithelial cells and those in rectal organoids from the same individual ( Silva et al., 2021 ). There are several published accounts of the use of nasal cultures in validating the relative efficacy of the new modulator combination in TRIKAFTA for rescuing F508del-CFTR and certain rare mutations ( Laselva et al., 2021a ; Veit et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients carrying the P67L- and L206W-CFTR mutations could benefit from the VX-661 + VX-445 corrector combination, which is so far not marketed separately, but may not necessarily profit from the addition of VX-770. This study adds to the growing number of publications, in which patient-derived HNE are used to study the modulator responses of rare CFTR mutants [ 27 , 31 , 32 , 33 , 58 , 59 , 60 , 61 , 62 ]. Our results suggest that HNE can not only be used to identify modulator responsive mutants, but also to optimize the modulator combinations for rare mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Pranke et al showed that CFTR chloride channel responses observed in patient-derived nasal epithelial cultures correlated with individual's improvement in Forced Expiratory Volume in the 1st second (FEV 1 ), i.e., the gold standard outcome to measure drug efficacy, measured after the treatment with a combination of Ivacaftor and the CFTR corrector Lumacaftor (Orkambi) [71,77]. Moreover, Amaral's group demonstrated a correlation between CFTR rescue by CFTR modulators in primary nasal epithelial cells and rectal organoids from the same individual [78].…”
Section: Airway Spheroids From Primary Airway Epithelial Cellsmentioning
confidence: 96%